Emotional contributions to the causal matrix of stuttering - Conture, Edward G. (Henry Stewart Talks, 2016)
Emotional contributions to childhood stuttering, Role of temperament in childhood stuttering, Overview of empirical findings (2000-2016), Children’s awareness of stuttering, Persistence of childhood stuttering, Suggestions in dealing with childhood stuttering